Inside implant criteria or not? – Detection of non-organic hearing loss during cochlear implant assessment. (1st November 2016) - Mistry, Sandeep G.; Carr, Simon D.; Tapper, Lynne; Meredith, Benjamin; Strachan, David R.; Raine, Christopher H.
Abstract : Objectives : The diagnosis of non-organic hearing loss (NOHL) is a difficult but important issue during the assessment process for cochlear implantation (CI). We aim to identify the key factors in identifying patients with NOHL during CI assessment and present our local screening protocol for NOHL. Methods : A retrospective review of patients referred to the Yorkshire Auditory Implant Service (YAIS) between 2003 and 2015 who were subsequently diagnosed with NOHL during the assessment. Patient demographic data, audiological and functional assessments were assessed. Results : Thirty-two patients were included in the study. Mean age was 43 years (range 14–82 years). Male to female ratio was 1:1.7. Indicators of possible NOHL included a sudden deterioration in hearing ( n  = 21; 66%), mismatches in observed behaviour and either pure-tone audiogram (PTA) ( n  = 27; 84%) or functional testing ( n  = 20; 80%) and stapedial reflexes below reported audiological thresholds ( n  = 12; 46%). A mismatch in functional hearing and PTA was seen in 72% of patients. Patients with suspected NOHL were referred for further objective testing. All 23 patients who underwent objective testing had better hearing levels compared to reported hearing thresholds thus placing them outside of implant criteria. Five candidates were found to have normal hearing thresholds. Discussion : NOHL can present a significant challenge to the implant team, particularly in the subgroup with a pre-existing organic hearing loss with non-organic overlay. We discuss the common features in this cohort of patients. Conclusions : To facilitate the identification of patients with NOHL, the YAIS has developed a screening protocol.